Controlling the interaction between optical solitons using periodic dispersion variations in an optical fibre. (30th November 2015) - Konyukhov, A I; Dorokhova, M A; Melnikov, L A; Plastun, A S
Abstract: This paper considers interaction between two fundamental optical solitons in an optical fibre with a periodically varying dispersion. Numerical simulation results indicate that, by properly adjusting the modulation period, one can change the type of interaction between solitons. We consider three particular cases: the fission of a soliton pair into two separate pulses, the generation of an intense pulse as a result of the fusion of two solitons and the formation of a coupled state of two solitons (soliton molecule). The present findings demonstrate the possibility of controlling the number and group velocity of solitons using passive single-mode optical fibres.